INVESTIGATION OF THE REACTION pp→ppsπ0 ON BASIS OF ONE PION EXCHANGE MODEL - Imambekov, O. (Recent Contributions to Physics, 2011)
Results of calculations of differential cross section of рр→{pp} process at the energy Тр=0-2 ГэВ sπ0 are presented in the work on the basis of one-pion exchange model. Cross section of elementary π0р→π0р subprocess is defined using electronic base of experimental data SAID. Comparison with available experimental data is spent. Position of the resonant maximum, character of power dependence and absolute size of the cross sections are reproduced well.